Empowering public health: building advanced molecular surveillance in resource-limited settings through collaboration and capacity-building - Koudokpon, Hornel; Lègba, Boris; Sintondji, Kevin; Kissira, Islamiath; Kounou, Arielle; Guindo, Ibrehima; Koné, Kléma Marcel; Abdou, Mahamadou; Koné, Amadou; Sambou, Claire; Bankolé, Honoré; Yadouleton, Anges; et al. (Frontiers in Health Services, 2024)
The rapid detection and continuous surveillance of infectious diseases are important components of an effective public health response. However, establishing advanced molecular surveillance systems, crucial for monitoring and mitigating pandemics, poses significant challenges in resource-limited developing countries. In a collaborative effort, research institutions from Benin joined forces with Mali's National Institute of Public Health to implement a state-of-the-art molecular surveillance system in Mali. This approach was characterized by collaboration, multidisciplinarity, and tutoring. Key activities included a comprehensive assessment of infrastructure and human resources through document reviews, interviews, and laboratory visits; the development and validation of Standard Operating Procedures (SOPs) for advanced molecular surveillance following an inclusive approach; capacity-building initiatives for 25 biologists in Mali on sequencing techniques; and international tutoring sessions for eight Malian professionals held in Benin. These collective efforts enabled Mali to establish an advanced molecular surveillance system aligned with the WHO’s global strategy for genomic surveillance. This manuscript aims to share experiences, insights, and outcomes from this initiative, with the hope of contributing to the broader discussion on strengthening global health security through collaborative approaches and capacity-building efforts, particularly in developing countries.